Submissions to the Australian and New Zealand Review of Food Labelling Law and Policy support traffic light nutrition labelling - John White; Louise Signal (Elsevier, 2012)
Abstract Objective: Food labels to support healthier choices are an important potential intervention for improving population health by reducing obesity and diet‐related disease. This study examines the use of research evidence about traffic light nutrition labelling in submissions to the Review of Food Labelling Law and Policy conducted in Australia and New Zealand. Methods: Content analysis of final submissions to the Review and a literature review of documents reporting research evidence about traffic light labelling. Results: Sixty‐two submitters to the Review were categorised as 'supporters' of traffic light labelling and 29 as 'opponents'. Supporters focused on studies showing traffic light labels were better than other systems at helping consumers identify healthier food options. Opponents cited evidence that traffic light labels were no better than other systems in this respect and noted a lack of evidence that they led to changes in food consumption. A literature review demonstrated that, as a group, submitters had drawn attention to most of the relevant research evidence on traffic light labelling. Both supporters and opponents were, however, selective in their use of evidence. Conclusions: The weight of evidence suggested that traffic light labelling has strengths in helping consumers to identify healthier food options. Further research would be valuable in informing the development of an interpretive front‐of‐pack labelling system. Implications: The findings have significant implications for the development of front‐of‐pack nutrition labelling currently being considered in Australia and New Zealand.